The [2+2] Cycloaddition‐Retroelectrocyclization (CA‐RE) Click Reaction: Facile Access to Molecular and Polymeric Push‐Pull Chromophores - Michinobu, Tsuyoshi; Diederich, François (Angewandte Chemie International Edition, 2018)
The [2+2] cycloaddition‐retroelectrocyclization (CA‐RE) reaction between electron‐rich alkynes and electron‐deficient alkenes is an efficient procedure to create nonplanar donor–acceptor (D‐A) chromophores in both molecular and polymeric platforms. They feature attractive properties including intramolecular charge‐transfer (ICT) bands, nonlinear optical properties, and redox activities for use in next‐generation electronic and optoelectronic devices. This Review summarizes the development of the CA‐RE reaction, starting from the initial reports with organometallic compounds to the extension to purely organic systems. The structural requirements for rapid, high‐yielding transformations with true click chemistry character are illustrated by examples that include the broad alkyne and alkene substitution modes. The CA‐RE click reaction has been successfully applied to polymer synthesis, with the resulting polymeric push‐pull chromophores finding many interesting applications. Only a click away: Nonplanar donor–acceptor (D‐A) chromophores can be prepared by click synthesis through [2+2] cycloaddition‐retroelectrocyclization (CA‐RE). This is a powerful method for producing functional molecular and polymeric systems for use in next‐generation electronic and optoelectronic devices.